Características morfogênicas e estruturais de trevo-persa (Trifolium resupinatum L.) em consórcio com azevém (Lolium multiflorum Lam.) submetidos a distintas alturas e intervalos de corte. - Rodrigues, Caroline Moreira (2010)
The aim of this study was to evaluate morphogenesis, structural and forage production of persian clover (Trifolium resupinatum L.) intercropped with ryegrass (Lolium multiflorum Lam) in the field, subjected to different heights and cutting intervals. The experiment was conducted during 2009 in the area ceded by Embrapa Clima Temperado in Capão do Leão, RS. Sowing was done by throwing in plots of 8 m2, with a density of 10 kg ha-1 of persian clover and 15 kg ha-1 of ryegrass. The design was randomized complete block design in a 3x3 factorial design with five replicates, totaling 45 experimental units. We used three cutting height, 4 cm, 8 cm and 12 cm and three cutting intervals, corresponding to the accumulation of heat 320, 420 and 520 GD. Technique was used in the branches / tillers marked and made ratings weekly in clover on count the number of leaves (open living, senescent, dead, emerged), number of nodes, plant height and length of branching, and in ryegrass on count the number of leaves (fully expanded, growing, senescent fully expanded, growing senescent dead), plant height and length of the tiller. On the occasion of the cuts was made that production of dry matter and botanical separation. The rate of leaf appearance (TAF) of Persian clover is modified by the interval (GD) and cutting height. Intervals of 320 and 420 GD have higher rates of leaf appearance (TAF) of Persian clover. The cutting height does not change the TAF of ryegrass. The range of GD 320 has a better TAF of ryegrass. In the cutting of 420 GD-Persian clover has a higher number of green leaves open fewer dead leaves, branches of greater length, greater number of nodes and greater forage production, and the recommended range for management by producers. The highest yield of intercropping forage ryegrass and Persian clover is obtained with GD 520 but with a high ratio stem / leaf.